Application of the stereotype content model to destination image: Evidence from residents of mainland China. (December 2019) - Shen, Xuerui; Lv, Xingyang; Lin, Shuang; Li, Chunxiao Spring
Abstract: It is important to determine the image tourists have of a particular destination, as this information can be used to enhance that destination's competitiveness. This study introduces the stereotype content model (SCM), from the field of social psychology, to the study of destination image. Empirical research, with a sample of residents from across mainland China as potential domestic tourists, on 31 provinces, municipalities and regions in China as tourist destinations verified that the two dimensions of 'warmth' and 'competence' in the SCM are relevant to the perception of a destination. Secondly, a cluster analysis showed that these 31 tourist destinations could be clustered into five different categories according to the respondents' evaluations of their warmth and competence, indicating that the SCM can be used to capture the content of destination image. Finally, regression analysis revealed significant relationships between these two dimensions of destination stereotype (warmth and competence) and visit intention. Highlights: Adopts the Stereotype Content Model to depict destination image from a two-dimensional structure of warmth and competence. Applies cluster analysis and regression analysis to analyse the primary data of 31 provinces, municipalities and regions in China. The two important dimensions of stereotype is of great use to differentiate and classify destinations as well as predict visit intentions.